Question
6-8. Simplify the following expressions. \( \begin{array}{ll}\text { a. }-\frac{3}{4}-\frac{2}{5} & \text { b. } \frac{1}{8}-\frac{2}{3}\end{array} \)
Ask by Cox Mcdonald. in the United States
Feb 03,2025
Real Tutor Solution
Tutor-Verified Answer
Answer
a. \( -\frac{23}{20} \) or \( -1 \frac{3}{20} \)
b. \( -\frac{13}{24} \)
Solution
Let's simplify each expression step by step.
### a. \( -\frac{3}{4} - \frac{2}{5} \)
1. **Find a common denominator:**
The least common multiple (LCM) of 4 and 5 is 20.
2. **Convert each fraction to have the common denominator:**
\[
-\frac{3}{4} = -\frac{3 \times 5}{4 \times 5} = -\frac{15}{20}
\]
\[
-\frac{2}{5} = -\frac{2 \times 4}{5 \times 4} = -\frac{8}{20}
\]
3. **Subtract the fractions:**
\[
-\frac{15}{20} - \frac{8}{20} = -\frac{23}{20}
\]
4. **Simplify (if necessary):**
\[
-\frac{23}{20} = -1 \frac{3}{20}
\]
**Final Answer for a:**
\[
-\frac{23}{20} \quad \text{or} \quad -1 \frac{3}{20}
\]
---
### b. \( \frac{1}{8} - \frac{2}{3} \)
1. **Find a common denominator:**
The least common multiple (LCM) of 8 and 3 is 24.
2. **Convert each fraction to have the common denominator:**
\[
\frac{1}{8} = \frac{1 \times 3}{8 \times 3} = \frac{3}{24}
\]
\[
\frac{2}{3} = \frac{2 \times 8}{3 \times 8} = \frac{16}{24}
\]
3. **Subtract the fractions:**
\[
\frac{3}{24} - \frac{16}{24} = -\frac{13}{24}
\]
4. **Simplify (if necessary):**
- The fraction \(-\frac{13}{24}\) is already in its simplest form.
**Final Answer for b:**
\[
-\frac{13}{24}
\]
Reviewed and approved by the UpStudy tutoring team
Like
error msg
Explain
Simplify this solution
Mind Expander
To simplify \(-\frac{3}{4} - \frac{2}{5}\), first find a common denominator, which is 20. Convert the fractions: \(-\frac{3}{4} = -\frac{15}{20}\) and \(-\frac{2}{5} = -\frac{8}{20}\). Now combine them: \(-\frac{15}{20} - \frac{8}{20} = -\frac{23}{20}\). For \(\frac{1}{8} - \frac{2}{3}\), the common denominator is 24. Convert the fractions: \(\frac{1}{8} = \frac{3}{24}\) and \(\frac{2}{3} = \frac{16}{24}\). Now subtract: \(\frac{3}{24} - \frac{16}{24} = -\frac{13}{24}\).